PENGARUH HUMAN RELATION, KERJASAMA TIM, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN: Studi Kasus pada PT Liebra Permana - Wahyu Puspita, Tiara; Qristin Violinda; Ratih Hesty Utami (JURNAL BISNIS KOLEGA, 2023)
This study aims to determine the influence of human relations, teamwork and communication on the performance of PT Liebra Permana employees. The approach used in this study is a quantitative approach. The population in this study is employees of PT Liebra Permana, the production department which amounts to 80 employees and the quality control section which amounts to 20 employees with the determination of samples taken using saturated sampling techniques. This study used multiple linear regression analysis with the help of SPSS 22.0 Software. The results of the analysis and discussion showed that human relations had a positive and significant effect on employee performance by 70.5%, teamwork had a positive and significant effect on employee performance by 46.5%, that communication had a negative and insignificant effect on employee performance by 15.6%. Simultaneously, human relation, teamwork and communication variables had a significant effect on employee performance by 73% and 27% were influenced by other variables outside the model specified in the study.